PARTISIPASI MASYARAKAT DALAM PENGELOLAAN WISATA ALAM AIR TERJUN PUCAK MANIK DI DESA WANAGIRI, KECAMATAN SUKASADA, KABUPATEN BULELENG - I Wayan Mertha; I Gede Tendi Kurniawan (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2017)
This study aims to determine the forms of participation and benefits perceived by local communities from their participation in the management of Nature Tourism Pucak Manik Waterfall in Wanagiri Village, Sukasada District, Buleleng Regency. This study uses quantitative design, with the number of samples of 56 members ofthe community involved directly or indirectly in the management of tourist attractions. This samples selected by purposive sampling technique. The survey method was used to collect data with a Likert scale questionnaire of degree five. The results show that the participation rate of local community in Wanagiri village is quite high, while the largest participation form is social participation with average value 3,89, and the lowest participation is the participation of property with the average value 2,37. The most perceived benefit of local community participation in the socio-cultural community is the growing sense of pride to remain in the village (stated by 83.9% of respondents), from the economic perspective of participation is expanding employment and business fields, expressed by 87.5% of respondents, and 89.3% of respondents said the environmental benefits of their participation were the identification of tourismpotentials in their area, and the government’s support in the development of Nature Tourism Pucak Manik Waterfall.